Resilience processes among youth newly diagnosed with HIV who live in urban informal settlements in Kenya: Implications for intervention. Issue 4 (2nd October 2019) - Harper, Gary W.; Lemos, Diana; Mutumba, Massy; Kumar, Manasi; Gikuni, Anne W.; Mustich, Iris; Hooks, Kylon; Hosek, Sybil G.; Ngugi, Elizabeth
Abstract: New HIV infections in Kenya are concentrated among youth ages 15–24. This study explores the lived experiences of youth newly diagnosed with HIV living in an urban informal settlement in Kenya in order to highlight their resilience processes. Five primary thematic areas of resilience processes emerged (1) changing personal perspectives about health and life; (2) changing personal behaviors to promote health and safety; (3) reaching out to supportive health care providers and organizations; (4) reaching out to family, friends, and partners; and (5) helping other youth. Results are discussed with regard to enhancing care for youth living with HIV in Kenya.